2023
DOI: 10.1111/crj.13598
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cases with hypersensitivity pneumonia: 10 year analysis

Abstract: Introduction The aim of this study was to examine the clinical features of hypersensitivity pneumonia (HP) cases, diagnostic methods, and related conditions in our hospital, which is a reference clinic in Turkey for chest disease. Methods The population of this retrospective cross‐sectional study consists of all hypersensitivity pneumonia patients followed in a tertiary hospital between 2010 and 2019. The data of 78 patients were included in the analysis. Data were grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…10 Conversely, a study conducted in Turkey by Adem et al showed a different pattern, with 52.6% of cases being male. 11 In our research, slightly over half of the participants (50.78%) did not exhibit any antibodies in the HP panel, while the remaining 49.22% tested positive for HP panel antibodies. This aligns with a study by the National Data Coordinating Centre in India, which found a prevalence rate of 47.3% for HP in India.…”
Section: Discussionmentioning
confidence: 46%
“…10 Conversely, a study conducted in Turkey by Adem et al showed a different pattern, with 52.6% of cases being male. 11 In our research, slightly over half of the participants (50.78%) did not exhibit any antibodies in the HP panel, while the remaining 49.22% tested positive for HP panel antibodies. This aligns with a study by the National Data Coordinating Centre in India, which found a prevalence rate of 47.3% for HP in India.…”
Section: Discussionmentioning
confidence: 46%